Composites of aluminum alloy and magnesium alloy with graphite showing low thermal expansion and high specific thermal conductivity. Issue 1 (31st December 2017) - Oddone, Valerio; Boerner, Benji; Reich, Stephanie
Abstract: High thermal conductivity, low thermal expansion and low density are three important features in novel materials for high performance electronics, mobile applications and aerospace. Spark plasma sintering was used to produce light metal–graphite composites with an excellent combination of these three properties. By adding up to 50 vol.% of macroscopic graphite flakes, the thermal expansion coefficient of magnesium and aluminum alloys was tuned down to zero or negative values, while the specific thermal conductivity was over four times higher than in copper. No degradation of the samples was observed after thermal stress tests and thermal cycling. Tensile strength and hardness measurements proved sufficient mechanical stability for most thermal management applications. For the production of the alloys, both prealloyed powders and elemental mixtures were used; the addition of trace elements to cope with the oxidation of the powders was studied. Abstract :